Investigation of significant industrial project delay factors and development of conceptual framework. Issue 1 (1st January 2021) - Abebe, Muluken; Germew, Sisay
Abstract: In developing countries, industrial projects play a vital role in achieving sustainable development. The late completion of projects suffers not only in the community but also the owners. The aim of the study is to investigates the main project delay factors and their impact on society, and the project owners. The factors are identified using the answers of 35 respondents, and are taken for a questionnaire. The respondents belong to investment office, commerce and industry office, contractors, clients, consultants, supervisors, and daily workers at the project site. Besides, interviews are taken. The relative importance index (RII) and Pareto analysis rule are used to analyze the data. It is found that among the 23 delay factors, the first 12 factors are significant. Both electric power shortage and finance approval progress contribute to the first top-two delay factors, as the Pareto 80/20 rule-based analysis demonstrates. A conceptual framework is developed to mitigate the impact of the delay. The major finding of the proposed framework can be used as a general framework to mitigate the impact of delay in all kinds of industrial projects.